2019
DOI: 10.1111/1556-4029.14130
|View full text |Cite
|
Sign up to set email alerts
|

Cases of Kava Impairment in Iowa Drivers

Abstract: Kava is an Oceanic plant in which the root is consumed as a beverage and is becoming increasingly popular. The effects of kava consumption may include sedation, euphoria, and impairment of motor coordination. This article demonstrates kava impairment through four cases of self‐reported kava use supported with Drug Recognition Expert (DRE) evaluations of each subject. Subject's urines screened negative for common drugs of abuse by immunoassay analysis. Urine from cases 3 and 4 were analyzed by liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…During the past 15 years, there have been a number of case reports in the literature about the potential adverse effects of kava where the product used was not reported or characterized. Berry et al reported four cases of drivers in Iowa unable to safely operate a motor vehicle, potentially due to kava use, between 2011 and 2018 [ 180 ]. There was no detailed information on the kava products or dosages (the amount of kavalactones) used.…”
Section: Safety Of Kava and Its Hepatotoxic Riskmentioning
confidence: 99%
“…During the past 15 years, there have been a number of case reports in the literature about the potential adverse effects of kava where the product used was not reported or characterized. Berry et al reported four cases of drivers in Iowa unable to safely operate a motor vehicle, potentially due to kava use, between 2011 and 2018 [ 180 ]. There was no detailed information on the kava products or dosages (the amount of kavalactones) used.…”
Section: Safety Of Kava and Its Hepatotoxic Riskmentioning
confidence: 99%
“…Hepatotoxic effects of Kava‐Kava have been reported, which are directly related to the raw material parts used, including mainly aerial parts (leaves and bark) of P. methysticum [81–83] . The consumption of kava‐kava has been shown to impair the ability to drive vehicles [84] …”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 99%
“…To date, there has only been one successful kava‐driving prosecution in NZ (District Court of New Zealand, ) and a small number overseas (Jolly, ; Swenson, ). Although this subject is of concern to road safety commentators (Berry, Gilbert, & Grodnitzky, ; Fu, Perl, Jennings, & Hepburn, ; Wainiqolo, Kool, Nosa, & Ameratunga, ), law enforcement, and land transport agencies in NZ and the Pacific Islands, the reality is that very little is known about the effects of kava at traditionally consumed volumes, on cognitive faculties related to driver safety. Additionally, when the comments of LaPorte et al's () and Sarris et al (2013) as discussed above are combined with Bwarenaba et al () concerns about kava psychopharmacology and neurophysiology following small pharmacologically administered doses of kava, this points to the urgency to undertake research in this field.…”
Section: Kava and Cognition Functionmentioning
confidence: 99%
“…To date, there has only been one successful kava-driving prosecution in NZ (District Court of New Zealand, 2000) and a small number overseas (Jolly, 2009;Swenson, 1996). Although this subject is of concern to road safety commentators (Berry, Gilbert, & Grodnitzky, 2019; Fu, Perl, Jennings, & Hepburn, 2019; Wainiqolo, Kool, Nosa, & F I G U R E 2 Chemical structure of the six major kavalactones present in kava beverage made from the roots and basal stump. Me = methyl group.…”
Section: Kava and Cognition Functionmentioning
confidence: 99%